The Concept of Human Unity and Islamic Inclusive Education: A Study of KH. Imam Zarkasyi’s Thought in Social Change - Dakir Dakir; Abdul Qodir; Umiarso El-Rumi (Institut Agama Islam Negeri Imam Bonjol Padang, 2017)
This study aims to identify and to analyze KH. Imam Zarkasyi’s paradigm model of thinking in increasing the value of inclusive Islamic education based on human unity value through historical-philosophical approach. The result is that the paradigm model of Tawhid Worldview constitutes rationality value to liberate science bigotry among tribes, ethnic, cultural or religious understanding. Rationality value to build scientific epistemology in Islamic education inclusive curriculum content can be implemented through the integration of social sciences culture of sources of Islamic teachings, the philosophy of Pancasila and socio-cultural diversity of learners locally, nationally and internationally. On the other hand, rationality value will change the learning approach and method, and civilizing values of inclusive education through religious communal environment. The paradigm model can balance value function and mental changes and inclusive personality of local, national and international Muslim generation.